Outcome Based Assessments for Private Pensions : A Handbook - Price, William; Ashcroft, John; Hafeman, Michael (World Bank, Washington, DC, 2016)
This handbook explains the outcomes-based diagnosis and assessment (OBA) framework for private pensions. The framework focuses on the pension outcomes that will improve people’s lives and how private pensions can help to improve these outcomes. The OBA is an integrated framework that addresses issues ranging from strategic vision and initial data requests to implementation and monitoring and evaluation. The diagnosis and assessment methodology combines theoretical insights with the practical work of a reviewer. Recommendations are tested against common implementation challenges to enhance deliverability. The Handbook provides a wide range of references to the literature that can be used to illustrate key issues with clients. It is intended as a first round diagnosis and assessment tool that identifies the most important areas on which to follow-up. So it helps to support a modular approach where priority areas are then addressed using more specialized tools.